2021
DOI: 10.3390/cancers13071522
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs, Long Non-Coding RNAs, and Circular RNAs: Potential Biomarkers and Therapeutic Targets in Pheochromocytoma/Paraganglioma

Abstract: Around 40% of pheochromocytomas/paragangliomas (PPGL) harbor germline mutations, representing the highest heritability among human tumors. All PPGL have metastatic potential, but metastatic PPGL is overall rare. There is no available molecular marker for the metastatic potential of these tumors, and the diagnosis of metastatic PPGL can only be established if metastases are found at “extra-chromaffin” sites. In the era of precision medicine with individually targeted therapies and advanced care of patients, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 93 publications
0
13
0
2
Order By: Relevance
“…Circular RNAs (circRNAs) are a type of endogenous non-coding RNA that do not have a 5′-cap or a 3′-polyA tail and are implicated in a variety of biological functions [ 6 , 7 ]. Recently, RNA-sequences revealed that circRNAs are involved in diagnosis, prognosis, development, and drug resistance in some tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a type of endogenous non-coding RNA that do not have a 5′-cap or a 3′-polyA tail and are implicated in a variety of biological functions [ 6 , 7 ]. Recently, RNA-sequences revealed that circRNAs are involved in diagnosis, prognosis, development, and drug resistance in some tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the versatile roles in a wide spectrum of biological processes, miRNAs can function as oncogenes or tumor-suppressors by regulating different targets. Recently the dysregulation of miRNAs was reported in a variety of malignancies, which was proposed as potential biomarkers or therapeutic targets [ 47–50 ]. Particularly, miRNAs were reported to regulate multiple phenotypes of GBM, such as cell proliferation, migration and invasion, self-renewal, angiogenesis and drug resistance [ 51–53 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNAs play different roles in cell regulation processes, such as biochemical reactions similar to those performed by enzymes; additionally, it is involved in complex regulatory functions that are related to the pathophysiology of various diseases [24,25]. Recently, the role of RNA mechanisms in epigenetic regulation and their implication in the pathogenesis of several tumors, namely long non-coding, miRNA, and Circular RNA (circRNA), has been highlighted.…”
Section: Rnamentioning
confidence: 99%